Otoritas Kepemimpinan Kyai dalam Membentuk Budaya Organisasi Religius - Moh Samsul Bahri; Ach Rizquha; Khoirul Umam (JUMPA : Jurnal Manajemen Pendidikan, 2021)
This research was conducted to examine the leadership of Khodimul Majlis Syubbanul Muslimin with qualitative research. Data collection techniques used are in-depth interviews, observation and documentation. In traditional leadership authority when obtaining legitimacy based on established beliefs in a tradition in society. On the other hand, it has also received legitimacy from those who exercise authority according to this tradition. In other words, traditional authority is based on traditional claims that there are virtues put forward by the leader and gains the trust of the followers based on the structural factors of the leader's heredity. Meanwhile, charismatic leadership authority has extraordinary charm, energy and character to influence others, so that it has an extraordinary number of followers (quantity) and bodyguards (followers) who are very loyal and dutifully devoted to it without reserve (quality).  From the research that has been done, the research results obtained are: by using Max Weber's Mobility theory, researchers found that the khodimul majlis syubbanul muslimin has Traditional Authority and Charismatic Authority.